Atypical Teratoid/Rhabdoid Tumor of the Central Nervous System in Children under the Age of 3 Years - Park, Meerim; Han, Jung Woo; Hahn, Seung Min; Lee, Jun Ah; Kim, Joo-Young; Shin, Sang Hoon; Kim, Dong-Seok; Yoon, Hong In; Hong, Kyung Taek; Choi, Jung Yoon; Kang, Hyoung Jin; Shin, Hee Young; et al. (Cancer research and treatment, 2021)
Purpose Atypical teratoid/rhabdoid tumor (ATRT) is a highly aggressive malignancy with peak incidence in children aged less than 3 years. Standard treatment for central nervous system ATRT in children under the age of 3 years have not been established yet. The objective of this study was to analyze characteristics and clinical outcomes of ATRT in children aged less than 3 years.Materials and Methods A search of medical records from seven centers was performed between January 2005 and December 2016.Results Forty-three patients were enrolled. With a median follow-up of 90 months, 27 patients (64.3%) showed at least one episode of disease progression (PD). The first date of PD was at 160 days after diagnosis. The 1- and 3-year progression-free survivals (PFS) were 51.2% and 28.5%, respectively. The 1- and 3-year overall survivals were 61.9% and 38.1%, respectively. The 3-year PFS was improved from 0% in pre-2011 to 47.4% in post-2011. Excluding one patient who did not receive any further therapy after surgery, 27 patients died due to PD (n=21), treatment-related toxicity (n=5), or unknown cause (n=1). In univariate analysis, factors associated with higher 3-year PFS were no metastases, diagnosis after 2011, early adjuvant radiotherapy, and high-dose chemotherapy (HDCT). In multivariate analysis, the use of HDCT and adjuvant radiotherapy remained significant prognostic factors for PFS (both p < 0.01).Conclusion Aggressive therapy including early adjuvant radiotherapy and HDCT could be considered to improve outcomes of ATRT in children under the age of 3 years.